IN VITRO EVALUATION OF ANTIOXIDANT POTENTIAL AND TOTAL PHENOLIC CONTENT OF BARLERIA LONGIFLORA LEAF EXTRACTS - JOTHIMUNIYANDI M,; JAYACHITRA A, (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of this present study is to estimate the antioxidant potential found in the leaves of Barleria longiflora that belongs to the family Acanthacea. Methods: Antioxidant activity of six different solvent extracts system of B. longiflora leaves was assayed for 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical activity, scavenging of hydrogen peroxide (H2O2), ferric reducing antioxidant activity, metal chelating ability assay, and total reducing ability. Total phenolic content of the extracts was determined by Folin–Ciocalteu method. Results: The radical scavenging activity was evaluated by DPPH of ethanol extract at concentration of 100 μg/mg was found to be 56.5% followed by methanol 48.4%, whereas maximum scavenging of H2O2 was observed in ethanol 83.4% followed by chloroform 70.8%. Ethanolic extract of B. longiflora leaves showed the highest value in ferric reducing antioxidant power assay 74.8%, metal chelating activity 61.6%, and total reducing ability 0.76±0.02 when compared to the standard ascorbic acid. Conclusion: The results suggest that the antioxidant potential of the ethanol extract has the highest activity in compared to other five extracts of B. longiflora leaves.